2013
DOI: 10.1111/cpf.12111
|View full text |Cite
|
Sign up to set email alerts
|

The effects of beta‐alanine supplementation on physical working capacity at heart rate threshold

Abstract: Beta-alanine (BA) supplementation has been shown to delay neuromuscular fatigue as a result of increased muscle carnosine concentrations. Carnosine has also been found in brain and cardiac tissue. The physical working capacity test at heart rate threshold (PWC(HRT)) is a global estimate of the onset of fatigue during exercise, influenced by central and peripheral factors. The purpose of this study was to determine the effects of 28 days of BA supplementation on the PWC(HRT). Thirty subjects (mean ± SD; age: 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…The effects of beta-alanine supplementation on time to exhaustion (TTE) are presented in Fig. 1 [ 3 , 22 , 54 – 60 ], with effects on fixed end-point exercise, such as races and time trials, presented in Fig. 2 [ 20 , 61 67 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of beta-alanine supplementation on time to exhaustion (TTE) are presented in Fig. 1 [ 3 , 22 , 54 – 60 ], with effects on fixed end-point exercise, such as races and time trials, presented in Fig. 2 [ 20 , 61 67 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 ). Using slightly different methodology to quantify neuromuscular fatigue, Smith-Ryan et al [ 60 ] found a modest (5.6 %) improvement of physical working capacity at heart rate threshold in young men and women consuming beta-alanine (RE = 111.9). The effects of beta-alanine on neuromuscular fatigue appear to be more pronounced in longer studies utilizing older subjects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To sustain endurance performance of the muscle the ability to deliver oxygen to the muscle and the ability of the muscle to utilise a given oxygen load for a sustained period of time (respiratory exchange rate) are important [ 87 ]. Maximal oxygen uptake (VO 2 max) as measured by breath-by-breath open-circuit spirometry is thus a well-established parameter to assess muscle performance [ 88 ]. VO2 max decreases with EIMUF but decreases also during age [ 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…A plateau of VO 2 , or 3. A respiratory exchange rate >1 [ 88 ]. Ventilatory threshold is defined as intersection of 2 regression lines (V E and VO 2 ) [ 88 ].…”
Section: Resultsmentioning
confidence: 99%